Implementing TaRL in physical education: Mastering specific skills in soccer games for junior high school students - Hartono, Mugiyo; Kurniawan, Wahyu Ragil; Wijayanti, Dwi Gansar Santi; Amran, Amran (Jurnal Cakrawala Pendidikan, 2025)
Teaching at the Right Level (TaRL) is one of the unique approaches adopted by the independent curriculum and has been widely applied in various countries, including Indonesia. This study aimed to determine the implementation of the TaRL approach in physical education, especially in teaching specific soccer skills in soccer games. The method used in this research is quantitative descriptive design, and the sample included 50 junior high school physical education teachers and 50 seventh-grade students. Data collection techniques included distributing questionnaires, conducting observations, and interviewing participants. The study concluded that, based on observations of PE lessons,76% of teachers had implemented the TaRL approach, and 72,80% of teachers responded positively to its application in achieving phase D learning objectives. Additionally, 88% of students responded positively to using TaRL in learning specific soccer skills. Interviews with several teachers and students supported these findings. The interviews revealed that TaRL enabled teachers to divide and organize class groups more effectively based on the needs and abilities of each student. Several students, particularly female students, reported feeling more comfortable and enjoying the process of learning specific skills and practices through the TaRL approach.